2013
DOI: 10.1093/qje/qjt022
|View full text |Cite
|
Sign up to set email alerts
|

The Transitional Costs of Sectoral Reallocation: Evidence From the Clean Air Act and the Workforce*

Abstract: This article uses linked worker-firm data in the United States to estimate the transitional costs associated with reallocating workers from newly regulated industries to other sectors of the economy in the context of new environmental regulations. The focus on workers rather than industries as the unit of analysis allows me to examine previously unobserved economic outcomes such as nonemployment and long-run earnings losses from job transitions, both of which are critical to understanding the reallocative cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
153
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 328 publications
(161 citation statements)
references
References 79 publications
4
153
2
2
Order By: Relevance
“…46 See Greenstone, List, and Syverson (2012) and Walker (2012) for recent evidence on the costs associated with the Clean Air Act.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…46 See Greenstone, List, and Syverson (2012) and Walker (2012) for recent evidence on the costs associated with the Clean Air Act.…”
Section: Resultsmentioning
confidence: 99%
“…For example, prior work has shown that while nonattainment designation reduces ambient concentrations of particulates, it does so at the cost of some economic competitiveness (Greenstone, 2002;Greenstone, List, and Syverson, 2012;Walker, 2011Walker, , 2012. Therefore, nonattainment may also contribute to declining economic conditions which may impact longrun earnings capacity of children born into those counties.…”
Section: Econometric Specificationmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence that environmental regulation also affects employment growth in regulated industries in the US [12]. Moreover, the costs of sectoral reallocation borne by individual workers may emerge not only in unemployment, but also in earnings losses after job changes [13]. In Europe, where labor markets are more regulated and layoffs more difficult, adjustment could also occur on the intensive margin of hours worked.…”
Section: Competing Interestsmentioning
confidence: 99%